How do online sales affect the transformation of the traditional bereavement service industry during the covid-19 pandemic? - Tan, Yen Thong (2022)
This research paper is investigating whether online sales could support the traditional bereavement service industry to achieve the transformation goal and let the Chinese community be aware of this industry. Besides, the transformation from traditional bereavement service to modern bereavement service can affect the behavioural of Malaysian Chinese community. Hence, it could help Malaysia to overcome the existing land constraints and environmental air pollution issues. The research method used in this project is quantitative research method. To avoid physical contact during the COVID-19 pandemic, the researcher conducted survey through distributing Google survey form to the respondents.